Aging Characteristics of ZSM-5 Zeolite on Low-Frequency Acoustic Applications - Mingbo Guo; Yijun Wang; Lei Zhang; Junran Lu; Chang Gong; Wanning Zhang; Yuxi Fang; Xinyuan Zhu; Shunai Che (Nanomaterials)
Zeolite is increasingly recognized for its enhancement of low-frequency acoustic performance in microspeakers. The aging characteristics of zeolite have been regarded as the critical factor for the commercial viability of mobile phones products, but the mechanism remains ambiguous. Here, the low-frequency acoustic performance of hierarchically structured ZSM-5 was investigated through aging with water and acetic acid (AA). It was discovered that water vapor augmented the resonance offset as it enhanced the structure of the zeolite, resulting in a lower water content. The resonance offset of ZSM-5 significantly decreased after the adsorption of AA vapor, as excessive AA was adsorbed through both physical and chemical adsorption, causing partial destruction of supermicropore and mesopores. The performance of ZMS-5 stored with vapor of AA and water mixture did not significantly deteriorate, indicating that water effectively protected the pores of zeolite to prevent excessive adsorption of AA. This was attributed to the fact that water was adsorbed by Brønsted acid sites of ZSM-5 more preferentially than AA, thereby avoiding excessive adsorption of AA.